Horse Meat Hydrolysate Ameliorates Dexamethasone-Induced Muscle Atrophy in C57BL/6 Mice via the AKT/FoxO3a/mTOR Pathway - Hee-Jeong Lee; Dongwook Kim; Yousung Jung; Soomin Oh; Cho Hee Kim; Aera Jang (Cells, 2025)
As life expectancy increases, muscle atrophy, characterized by a decline in muscle mass and strength that can impair mobility, has become a growing concern, highlighting the potential of protein supplementation as a promising intervention strategy. A horse meat hydrolysate, with a molecular weight of less than 3 kDa, derived from m. biceps femoris and produced using the food-grade enzyme Alcalase® (A4 < 3kDa) was evaluated for its efficacy in mitigating dexamethasone-induced muscle atrophy, a widely accepted model for studying catabolic muscle loss. Administered orally to C57BL/6 mice at dosages of 200 mg/kg or 500 mg/kg body weight for 35 days, A4 < 3kDa effectively countered the weight loss induced by dexamethasone in the whole body, quadriceps, tibialis anterior, and gastrocnemius muscles. Moreover, it increased muscle fiber cross-sectional area and grip strength. These effects were attributed to increased protein synthesis via the protein kinase B (AKT)/forkhead box O3 (FoxO3a)/mammalian target of rapamycin (mTOR) signaling pathway. A4 < 3kDa augmented the phosphorylation of key components of the signaling pathways associated with muscle atrophy, resulting in reduced mRNA expression of Atrogin-1 and MuRF-1. These findings demonstrate the potential of A4 < 3kDa as a functional food ingredient for preventing muscle atrophy.